Emotion and Psychophysiological Responses During Emotion–Eliciting Film Clips in an Eating Disorders Sample - French, Melanie N.; Chen, Eunice Y. (Frontiers in Psychology, 2021)
Background: Greater vulnerability to negative emotions appear associated with the development and maintenance of eating disorders (EDs). A systematic review of psychophysiological studies assessing differences in responses to emotion-eliciting film clips between individuals with and without EDs reveals that there are no studies that have examined the effect of standardized validated film clips on psychophysiological response across a range of EDs. Methods: Using standardized validated film clips, the present study examined self-reported emotions and psychophysiological responses of women with Binge-Eating Disorder (BED; n=57), Anorexia Nervosa (AN; n=16), Bulimia Nervosa (BN; n=34) and HCs; n=26) at Baseline, during Neutral, Sad, Happy, and Fear-inducing film clips, and at Recovery. Results: Throughout the protocol, the ED groups reported significantly greater negative emotions than HCs. BN and BED groups reported more frustration than the HC group. Compared to HCs, the BED group reported stronger urges to binge throughout the protocol, whereas BN group reported stronger urges to binge relative to the HC group only at Baseline and Recovery. The BN and BED groups experienced decreased urges to binge during all film clips compared to Baseline. Respiratory Sinus Arrhythmia levels were significantly lower in the BED group compared to HCs and the BN group throughout the protocol. Discussion: Standardized validated film can be used to elicit expected self-reported emotion and skin conductance responses in ED groups although individuals with EDs compared to individuals without EDs report greater negative emotions. Despite self-reported negative emotions, interestingly film clips appeared to reduce urges to binge in binge-eating groups.